2023
DOI: 10.3389/fphys.2023.1151151
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gut bacterial community composition between modern and slower-growing broiler breeder lines: Implications of growth selection on microbiome composition

Abstract: In the last century broiler chicken lines have undergone an extensive breeding regime aimed primarily at growth and high meat yield. It is not known if breeding has also resulted in a change to the broiler breeder’s associated gut microbiota. Here we compared the gut microbiota of 37-week-old commercial Cobb breeding dams with dams from a broiler Legacy line which has not undergone selection since 1986. The dams from both lines were kept together in the same shed under the same management protocol from day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Thus, it is possible that the differences in the reproductive tract microbiome between the Legacy and Cobb hens shown here are a result of physiological differences affecting the gut environment rather than the reproductive tract environment. However, differences in the orders Pseudomonadales, YS2 and RF32, reported in this work, were not found in previously reported cecum samples ( 13 ) and may imply additional differences also in the reproductive tract environment.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Thus, it is possible that the differences in the reproductive tract microbiome between the Legacy and Cobb hens shown here are a result of physiological differences affecting the gut environment rather than the reproductive tract environment. However, differences in the orders Pseudomonadales, YS2 and RF32, reported in this work, were not found in previously reported cecum samples ( 13 ) and may imply additional differences also in the reproductive tract environment.…”
Section: Discussioncontrasting
confidence: 74%
“…Indeed, the analysis described for both breeds analyzed here reaches the same conclusion. Here it was shown that the order Verrucomicrobiales was found to be significantly higher in the infundibulum and magnum of Cobb dams, and Lactobacillales was significantly lower in the infundibulum, mirroring the significant differences shown in the comparison of the cecum microbiota of the two breeds ( 13 ). Furthermore, Bacteroidales which was found to be significantly higher in the infundibulum of Cobb dams was also high in the cecum of Cobb dams, though not significantly so.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations